2022
DOI: 10.3390/cancers14164056
|View full text |Cite
|
Sign up to set email alerts
|

The m6A-Related Long Noncoding RNA Signature Predicts Prognosis and Indicates Tumor Immune Infiltration in Ovarian Cancer

Abstract: Background: OV is the most lethal gynecological malignancy. M6A and lncRNAs have a great impact on OV development and patient immunotherapy response. In this paper, we decided to establish a reliable signature of mRLs. Method: The lncRNAs associated with m6A in OV were analyzed and obtained by co-expression analysis of the TCGA-OV database. Univariate, LASSO and multivariate Cox regression analyses were employed to establish the model of mRLs. K-M analysis, PCA, GSEA and nomogram based on the TCGA-OV and GEO d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 74 publications
0
7
1
Order By: Relevance
“…These findings imply that WAC-AS1 is downregulated with the occurrence and development of brain glioma, and no longer plays a protective role in the prognosis of this disease. WAC-AS1 has been identified as a protective factor in ovarian carcinoma, which contrasts with our results [ 9 , 24 ]. Although we observed a similar trend for a protective role of WAC-AS1 in patients with OV, the Kaplan–Meier survival analysis indicated that there was no significant difference in survival between patients with high and low WAC-AS1 expression.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings imply that WAC-AS1 is downregulated with the occurrence and development of brain glioma, and no longer plays a protective role in the prognosis of this disease. WAC-AS1 has been identified as a protective factor in ovarian carcinoma, which contrasts with our results [ 9 , 24 ]. Although we observed a similar trend for a protective role of WAC-AS1 in patients with OV, the Kaplan–Meier survival analysis indicated that there was no significant difference in survival between patients with high and low WAC-AS1 expression.…”
Section: Discussioncontrasting
confidence: 99%
“…AL122125.1 emerged as an independent prognostic factor, providing novel information about LUSC risk-stratification ( 63 ). Similar approach has also been applied for the analysis of bladder, colon cancers, hepatocellular carcinoma and hematological malignancies, in particular like acute myelocytic leukemia ( 28 , 64 73 , 77 , 78 ).…”
Section: M6a-related Lncrnas Signaturesmentioning
confidence: 99%
“…When integrated with clinical characteristics, the model exhibited enhanced predictive efficacy compared to the standalone signature (Figure 5). Notably, among clinical characteristics integrated prognostic signatures, this signature exhibits a high AUC value of ROC curve, surpassing the predictive performance of both the endoplasmic reticulum stressrelated gene signature and the m6A-related lncRNA signature in OV [41,42]. In summary, the ubiquitin-related signature showed a satisfactory prognostic value for patients with OV.…”
Section: Advances Of the Ubrgs Signature For Prognostic Prediction In Ovmentioning
confidence: 87%